IDENTIFICATION OF SELETIVE CLAUDIN CATION CHANNEL BLOCKERS. (21st January 2021) - Ma, Jingjing; Wu, Emma; Li, Ye; Seibel, William; Shen, Le; Khalili, Fatemeh; Weber, Christopher
Abstract: Compromised epithelial barrier function is known to be associated with inflammatory bowel disease (IBD) and may contribute to disease development. One mechanism of barrier dysfunction is increased expression of paracellular tight junction ion and water channels formed by claudins. Claudin-2 and -15 are two such channels. We hypothesize that blocking these channels could be a viable therapeutic approach to treat diarrhea. In an effort to develop blockers of these channels, we turn to our previously developed and validated in silico models of claudin-15 (Samanta et al. 2018). We reasoned that compounds that can bind with the interior of claudin pores can limit paracellular water and ion flux. Thus, we used docking algorithms to search for putative small molecules that bind in the claudin-15 pore. AutoDock Vina was initially used to assess rigid docking using small compound databases. The small molecules were analyzed based on binding affinity to the pore and visualized using VMD for their potential blockage of the channel. Clusters of binding modes were identified based on the prominent interacting residues of the protein with the small molecules. We initially screened 10, 500 compounds from within the UIC Centre for Drug Discovery and a cross-section of 10, 000 compounds from the NCI open compound repository. This initial screen allowed us to identify 2 first-in-class selective claudin-15 blockers with efficacy in MDCK monolayers induced to express claudin-15 and in wildtype duodenum. Next, we screened the entire NCI open compound repository for additional molecules structurally related to our best initially identified molecule and this has allowed us to identify 13 additional molecules that increase TER of claudin-15 expressing MDCK monolayers by 90–160%. Additionally, these molecules possess similar structural components that will be collected in a fragment library and explored through molecular dynamics simulations. We also developed a claudin-2 homology model on which we are performing docking studies and in vitro measurements, which we expect will result in similar candidate ligands for blocking claudin-2. Our study will provide important insight into the role of claudin-dependent cation permeability in fundamental physiology, which we believe will lead to the utility of claudin blockers as a novel and much needed approach to treat diseases such as IBD.